(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The search deals with an analytical Study of the Standard of living of the Syrian Citizens .First , the Research aims to study the Standard of living for the period before the war on Syria which extended between years 2000-2010 . Then it deals with the living standard after year 2011 through the study of several indications such as : cost of living , income distribution , family budget and analysis the reasons that led to the deterioration of the standard of living either those relating to the circumstances of war as the loss the government of the most important of financial resources represents in the petroleum Wells , or those related to the exchange rate . The research also aims to analyze and evaluation of the Government measures to face the deterioration from two points of view; one believes the success of the government giving its supports, other believes the fail of the government giving its supports too. Also , the Search aims to study the social reflection of the low standard of living related to increase of crime rates or the low level of education . Finally, the study provided a set of proposals that help in improving the standard of living, some of them are related to the mechanism of meeting the needs of the Syrian citizen from the basic provisions , while others related to the mechanism of managing the monetary market and exchange . The Search depended upon the Statistical analysis systematic in the study. The Study reached to set of results the most of connected to the low of the actual monetary income with about 88% and the low of living level by which 85% of people under the level of poverty and this due to several reasons some of which related the Exchange rate and others related the government failure to control the prices.